PERANCANGAN APLIKASI PEMBELAJARAN GEOGRAFI BERBASIS ANDROID - Damanik, Erika Meylina; Suharyanto, Cosmas Eko (Computer Science and Industrial Engineering, 2020)
In the modern era, the development of technology is no doubt. Where humans always find new innovations to create new inventions or upgrading old technology capabilities to something more esophisticated thanprevious technology. A form of technological progress that plays a major role in life modern namely Android-based Smartphone. At the Emarketer digital research Institute explained that in 2018 an estimated number of active Smartphone users more than 100,000,000 people out of a population of 250,000,000, and is expected to become the fourth Smartphone consumer after China, India and the United States (Solikin, Informatics, Vocational & Palembang, 2018). Therefore, the presence of a Smartphone can be a business opportunity for education. Smartphone can be used as a creative, innovative and interactive learning media. The use of Smartphones in the world of education is a positive step for para students to get education outside formal school hours. To compensate presentation of various types of applications that are less useful that is usually played by the para students, the authors create an application in the form of general knowledge about geography lessons that also take part in current technological developments.